Sistem Kesejahteraan Tenaga Pendidik dan Tenaga Administrasi Sekolah di SMP Negeri 31 Bandung - Jarwo, J (Universitas Pendidikan Indonesia, 2023)
This research aims to analyze the level of welfare obtained by the workforce at Junior High School 31 Bandung, both in terms of material (wages, allowances and bonuses/rewards) and non-material (facilities) at Junior High School 31 Bandung. This research uses a qualitative approach, with descriptive data collection techniques. The data used in this research was obtained from direct observations and interviews with related sources. The results of this research show that (1) the level of welfare of the workforce, both educators and educational staff at Junior High School 31 Bandung is sufficient, both in terms of salary which follows the regional minimum wage (UMR), allowances and incentives/rewards (2) SMPN 31 Bandung is also provide many adequate allowances and facilities to employees at Junior High School 31 Bandung in order to improve the welfare of the workforce, both educators and education staff. (3) The level of employee job satisfaction at Junior High School 31 Bandung is categorized as quite high, this is shown by the suitability of the salary to the workload received by the employee, the condition of the school environment and the attitude of the leader and co-workers which is good and in line with expectations so that the impact is comfort. and employee satisfaction at work..